(untitled) (Development Engineering Conferences Center Articles Database, 2024)
The traditional buildings of Iran and the world have various characteristics, and one of these characteristics is the acoustic characteristics of these buildings. In the past, since the technical knowledge of acoustic engineering did not exist with the current quality, designers, and builders used different methods to solve the acoustic issue of these buildings for different applications. There is still no detailed information about their design and implementation methods. However, in this article, the acoustic characteristics of some religious buildings of the past in Iran and the world have been investigated. By choosing one of them as the most complete method and in a way with the most targeted acoustic design, we analyze and reverse engineer this building. It can be said that among Iranians and tourists who visit Iran’s historical monuments. The acoustic feature of Isfahan Shah Mosque has unique features. In this building, when a person sings or speaks on a marked stone under the ground, the sound is heard with better quality in other parts of the mosque’s naves. In this research, this building belonging to the Safavid era will be subjected to a detailed acoustic analysis so that the method considered in this method can be used in today’s architecture, especially sustainable architecture.